1997
DOI: 10.1063/1.474606
|View full text |Cite
|
Sign up to set email alerts
|

The OBrO C(2A2)←X(2B1) absorption spectrum

Abstract: The highly structured visible absorption spectrum of the bromine dioxide radical, OBrO, has been observed in the 15 500-26 000 cm Ϫ1 region. The spectrum is dominated by a long progression in the Br-O symmetric stretching motion (1 Ј) and a series of short progressions built on the bending mode (2 Ј); there are no features associated with the excitation of the antisymmetric stretching mode (3 Ј). The spectrum also contains numerous transitions originating from the ͑0,1,0͒ and ͑1,0,0͒ vibrational levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
75
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(98 citation statements)
references
References 34 publications
23
75
0
Order By: Relevance
“…1-5 represent transitions from the ground state of the anion (closed-shell) to • are distributed among 26 MOs with the following configuration in the ground state: X 2 B 1 : core (14a 1 ) 2 (2b 2 ) 2 (3a 2 ) 2 (7b 1 ) 1 . 31 The microwave spectrum was analyzed to yield a bent molecule with Br-O bond length of 1.649 Å and O-Br-O bond angle of 114.44 • . 81 The extra electron for the BrO 2 − anion is expected to reside on the singly occupied MO, 7b 1 , to form a closed-shell ground state ( 1 A 1 ).…”
Section: Spectral Assignment and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1-5 represent transitions from the ground state of the anion (closed-shell) to • are distributed among 26 MOs with the following configuration in the ground state: X 2 B 1 : core (14a 1 ) 2 (2b 2 ) 2 (3a 2 ) 2 (7b 1 ) 1 . 31 The microwave spectrum was analyzed to yield a bent molecule with Br-O bond length of 1.649 Å and O-Br-O bond angle of 114.44 • . 81 The extra electron for the BrO 2 − anion is expected to reside on the singly occupied MO, 7b 1 , to form a closed-shell ground state ( 1 A 1 ).…”
Section: Spectral Assignment and Discussionmentioning
confidence: 99%
“…The first spectroscopic study (visible absorption) of gas phase BrO 2 was reported by Rattigan et al 25 Since then, a numbers of studies have been devoted to investigate the properties of BrO 2 experimentally employing a variety of techniques, [23][24][25][26][27][28][29] including: rotational spectroscopy, 26 visible absorption in solid matrices, 27, 28 photoionization, 19,29 and high-resolution ultraviolet/visable (UV/Vis) absorption spectroscopy. 30,31 The highly structured visible absorption spectrum of bromine dioxide radical, OBrO, observed in the 15 500-26 000 cm −1 region by Miller et al, 31 was augmented by Franck-Condon simulations and high-level ab initio calculations, and concluded due to the dipole-allowed C( 2 A 2 ) ← X( 2 B 1 ) electronic transition. Several theoretical investigations have been conducted to study the molecular structure, vibrational spectra, and energetics of BrO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations